Pengaruh Pemberian Pilates Exercise Terhadap Penurunan Nyeri Menstruasi Primer Pada Remaja Usia 18-21 Tahun - AMELLIA, MARINDA, Wahyuni, SSt.FT.M.Kes, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2015)
Background: Dysmenorrhea is set of manifestations painful that appear during of before first menstrual circle, usually pain (cramps) in stomache that happen 24-36 hours, because was happen decrease prostaglandins hormone exaggerate. Pilates Exercise is physical exercise that focus in strengthening, flexibility, muscle control, improved posture, and breathing. Objective: To determine the influence of pilates exercise for decrease menstrual pain/ primary dysmenorrhea in adolescent 18-21 years. Type of research: Quasi experimental with control group pre and post methods, 15 respondents in treatment group and control group. Pilates exercise giving for 3 weeks with frequency 3 times a week for 50 minutes. Pain was measured using NRS. Data were analyzed using SPSS with Wilcoxon test and Mann Whitney test. Result: There are influence pilates exercise for decrease menstrual pain/ primary dysmenorrhea in adolescent 18-21 years, after using wilcoxon test in treatment group obtained the value 0,001, while in control group obtained the value 0,033. Mann Whitney test obtained p value 0,001 are availability different influence between treatment group and control group for increase menstrual pain/ primary dysmenorrhea in adolescent 18-21 years. Conclusion: There are influence pilates exercise for decrease menstrual pain/ primary dysmenorrhea in adolescent 18-21 years. Keywords: Menstrual pain/ primary dysmenorrhea, pilates exercise.